Laparoscopic Intra Peritoneal Onlay Mesh Plus (IPOM Plus) repair of Ventral Hernias – Experience in a Tertiary Hospital - Haque, Md Rezwonul; Alam, Muhammed; Hossain, SM Shakhwat; Khan, Lutfunnahar; Islam, Mohammed Aminul (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Introduction: Laparoscopic Ventral Hernia Repair (LVHR) was first described by Karl Leblanc in 1992 and has increasingly been gaining popularity in this present era of minimal access surgery. Laparoscopic Intraperitoneal Onlay Mesh (IPOM) repair with its modification intraoperative Onlay Mesh Plus (IPOM Plus) repair is now being well-accepted option for the treatment of ventral hernias. Objective: To assess the safety and efficacy of the laparoscopic IPOM plus modality in the management of ventral hernias. Methods: This is a descriptive observational study, carried out on 22 patients who underwent Laparoscopic ventral hernia repair by IPOM Plus technique between January 2017 to December 2018 at CMH Dhaka. Patients who had ventral hernia with a defect size> 2 cm but < 10 cm were included in this study. Primary subcutaneous transfascial suture closure of all ventral hernias with defect size >2 cm were done using prolene 1-0.Optimized composite mesh (ParietexTM) and Polymesh composite partially absorbable mesh were used as prosthesis anchored with four corner sutures and fixed with non absorbable tacking device. Follow up period was one year. Results: A total of 22 patients underwent Laparoscopic IPOM Plus repair of ventral hernias. Intraoperative and postoperative complications were negligible. No seroma, bulging of mesh, intestinal obstruction, mesh infection and recurrence observed in one year follow up time. But one patient developed de novo spigelian hernia on the right side outside the mesh system after one year. One patient (4.5%) developed post operative persisting pain requiring analgesic at 2 months. Conclusion:: Laparoscopic IPOM plus repair of ventral hernia is a safe, effective and well accepted modality. J Bangladesh Coll Phys Surg 2023; 41: 150-155